POLA ASUH GIZI PADA ANAK BALITA DENGAN PERTUMBUHAN BAIK (TUMBUH KEJAR DAN TUMBUH NORMAL) DI KECAMATAN ARJASA KABUPATEN JEMBER (POSITIVE DEVIANCE) - Sulistiyani Sulistiyani; Ni'mal Baroya (Jurnal Ilmu Kesehatan Masyarakat, 2009)
The child caring constitutes the deeds conducted by their family (mother, father, grand mother or other person) in giving the food, taking care of the health, giving stimulate and emotional support required for growth and development. Arjasa is one of the sub districts having high percentage of poor families and a nutrition vulnerable area. However, we can still find children under five years of age having good nutrition status. This is the reason why the writer is interested in studying further about the case of how among the aforesaid poor families are still able to prioritize the nutrition for their under five year children (positive deviance). The first step taken in this research was selected the subject of research by using the purposive method. It was intended to get the subject with the criteria of mothers from poor families, having the children of 6 to 59 months of age with good nutrition status and in possession of Kartu Menuju Sehat/KMS (Growth Monitoring Chart). The second step was carried out exploration. It was intended to explore and in this research three approaches had been applied, namely by combining the three methods of in depth interview, documentation study, and observation to cross check the data as well as to keep validity of the data. The third step taken in this research was applied the qualitative analysis. It was intended to analyze the practice of nutrition caring pattern by the family upon good nutrition status on children of 6 to 59 months of age at the poor families (positive deviance) at Sub-district of Arjasa, Regency of Jember. The result of this research showed that the factors that influence positive deviance at Sub-district Arjasa is the role of health officer, in this case is midwife in giving motivation to others, whether through certain approach at Posyandu or through individual approach. Keywords:Nutrition caring pattern, good growth